Effect of hydraulic residence time and inlet flow distribution ratio on the pollutant removal of low‐temperature municipal wastewater in multistage AO process. (14th May 2020) - Wang, Fan; Li, Jun; Bian, Dejun; Nie, Zebing; Ai, Shengshu; Tian, Xi; Wang, Hongliang
Abstract: Low temperature environment was one of the difficulties in sewage treatment. In this study, the removal efficiency of multistage AO process was analysed under different hydraulic residence time (12 h, 8 h and 6 h) and inlet flow distribution ratio(5 : 4 : 4, 3 : 2 : 1 and 25 : 15 : 6), the rules of pollutant migration and transformation were compared and analysed under different control parameters. The results show that enhanced nitrogen removal and optimised organics utilisation were obtained simultaneously in the feeding process with hydraulic retention time of 8 h as well as influent distribution ratio of 3 : 2 : 1. HRT and inlet flow distribution ratio affect nitrogen load and organic matter distribution in each stage of the multistage AO system, the removal efficiency of ammonia nitrogen in each stage of the system was more than 80% under optimal conditions, the total nitrogen removal rate was more than 80%, among which the synchronous nitrification and denitrification account for 29.50%.